PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SDN 004 TEMBILAHAN KOTA - Nurbaini, Nurbaini (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is based on the low level of mathematics learning result of grade 3 students of SDN 004Tembelihan Kota. Based on this, the researcher performs improvement of learning process by applying STADtype cooperative learning model. This research was conducted in SDN 004 Tembilahan Kota, the subject of thisresearch is the third grade students with the number of 23 students. Based on the research results obtained datathat after the implementation of cooperative model type STAD student learning outcomes have increased on thebasic score of the number of students who complete is 8 students with an average score of 58.41. In cycle I thetotal number of completed students is 16 students with an average score of 71.14. And in cycle II the number ofcompleted students is 22 students with an average score of 84.32.